2012
DOI: 10.1007/s00737-011-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and depression among new mothers at 8 months later of the 2008 Sichuan earthquake in China

Abstract: On May 12, 2008, a magnitude 8.0 earthquake struck China's southwestern Sichuan province. Recent studies have identified mental health problems among the survivors, but little is known about the impact of the Sichuan earthquake on the mental health of new mothers in the area. The main objective was to assess the impact of the Sichuan earthquake on the posttraumatic stress disorders (PTSD) and depression of new mothers. A total of 317 new mothers were interviewed in the hospital from January 2009 to March 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…In particular, depression among adolescents after earthquakes has attracted growing interest (e.g., Giannopoulou et al, 2006; Goenjian et al, 2011), because of the observed susceptibility of adolescents to trauma following natural disasters (e.g., Margolin et al, 2010). Prevalence rates for depression have ranged from 13.6 to 51.3% in adolescents exposed to earthquakes (e.g., Kolaitis et al, 2003; Fan et al, 2011; Qu et al, 2012; Ying et al, 2014). The aim of this study was to examine possible predictors and underlying mechanisms for post-earthquake depression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, depression among adolescents after earthquakes has attracted growing interest (e.g., Giannopoulou et al, 2006; Goenjian et al, 2011), because of the observed susceptibility of adolescents to trauma following natural disasters (e.g., Margolin et al, 2010). Prevalence rates for depression have ranged from 13.6 to 51.3% in adolescents exposed to earthquakes (e.g., Kolaitis et al, 2003; Fan et al, 2011; Qu et al, 2012; Ying et al, 2014). The aim of this study was to examine possible predictors and underlying mechanisms for post-earthquake depression.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted after the Pakistani earthquake found that 63% of the earthquake-affected women of reproductive age had anxiety and 54% showed signs of depression [25]. Eight months after the Sichuan earthquake, the prevalence of depression was found to be 29.0% among postpartum women [26]. Goenjian and colleagues found that 32-months after the 1999 Parnitha earthquake in Greece, 13.6% of adolescents still met the criteria for clinical depression.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the 1988 Armenian earthquake reported that 52% of adult survivors met the criteria for depression [11]. Corresponding risk factors were identified in these studies for the different groups being surveyed [26,27]. For example, unemployed women, those with a lower monthly family income, and those who suffered from poor sleep were found to have a higher risk of depression [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PTSD symptoms, child exposed to traumatic events usually experience comorbid depression. For example, previous studies reported that the prevalence rates of depression ranged from 13.6% to 40.8% in children exposed to an earthquake [1,[6][7][8]. The disparity in rates of PTSD and depression across studies could be attributed differences in the severity of traumatic events, the timing of psychiatric assessment, and the diversity of the research methodologies employed [9,10].…”
Section: Introductionmentioning
confidence: 99%